Chicago [videorecording (Blu-Ray)] - Condon, Bill, 1955-; Gere, Richard, 1949-; Zellweger, Renée, 1969-; Zeta-Jones, Catherine, 1969-; Queen Latifah, 1970-; Diggs, Taye (Paramount, 2020)
Based on the popular Broadway musical. Two murderous women strive for the spotlight in 1920s Chicago.